Refugium peccatorum: The Virgin Mary’s Saving Protection in Medieval Liturgical Hymns - José María Salvador-González (Religions)
The current article does not directly study the liturgical ritual as a set of gestures and forms of ceremonial behavior. Instead, it focuses on shedding light on the doctrinal content of many Mariological liturgical hymns, precisely the conceptual basis that gives meaning to the corresponding Marian liturgical rituals. Based strictly on the study of primary sources of Christian doctrine, this article aims to highlight the belief in the help, protection, and mediation of the Virgin Mary on behalf of human beings as reflected in countless medieval Latin liturgical hymns. The article is divided into two central parts: in the first, the author presents, in the original Latin and its English translation, an extensive series of fragments of liturgical hymns that develop the Mariological belief; in the second, he summarizes the primary doctrinal meanings and emotional attitudes that hymnographers reflect when poetically reconfiguring this belief in their hymns. Following the conclusion, the article catalogs the abundant sequence of Christian primary sources used in this research.